Pedagogical Conditions for Improving Research Activity in Future Primary School Teachers - Radzabova, Komilovna Nodirabegim (International Journal of Human Computing Studies, 2022)
This article describes the pedagogical conditions in our research as a social pedagogical necessity to improve the research activities of future primary school teachers - a set of objective and subjective factors existing in the higher education system that determine the appropriate content, organizational form and methods of active involvement of students in research.